The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/gcc.10022
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide search for loss of heterozygosity in Burkitt lymphoma cell lines

Abstract: The molecular biological characteristics of Burkitt lymphoma (BL), in addition to the presence of the Epstein-Barr virus (EBV) in some forms, relies on well-characterized alterations, such as MYC translocations and TP53 inactivations. To ascertain the number and location of other genome alterations, we used 191 polymorphic markers in a genome-wide search for loss of heterozygosity (LOH) in 31 Burkitt lymphoma cell lines and their normal counterparts. We were able to distinguish two types of altered allelic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Mutations in the P53 gene have been found in at least 33% of BL biopsy specimens [51] and in as much as 83% of BL cell lines [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the P53 gene have been found in at least 33% of BL biopsy specimens [51] and in as much as 83% of BL cell lines [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…9 The human FCRL1 gene is located at chromosome region 1q21 where genome abnormalities including translocations frequently occur in various B-cell malignancies. [29][30][31] For FCRL5 (IRTA2), the expression levels are on average 10-fold higher in 1q21 abnormal cell lines. 8,32 In this study, high expression of FCRL1 expression on CLL cells was noticed.…”
Section: Discussionmentioning
confidence: 99%
“…19 As controls, we used the parent cell lines BJAB, 39,40 BL41, and DG75, which do not contain EBNA2-estrogen receptor transgene. Regarding the status of 1q21 aberrations, BJAB is not known to have any, 28 while BL41 does have limited 1q abnormalities which do not appear to include 1q21-25; 41 the status of 1q21 in DG75 cells is unknown. All cells were cultured in RPMI-1640 (HyClone, Logan, UT) containing 10% fetal bovine serum (HyClone), 2 M L-glutamine, 100 U/mL penicillin, 100 g/mL streptomycin, and nonessential amino acids.…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…28 Furthermore, a genome-wide search for chromosomal abnormalities concluded that a gene important for Burkitt lymphoma pathogenesis is located in region 1q21-25, and overexpression of this gene mimics the effects of EBV. 41 As FcRH5 is encoded on 1q21 and is induced by EBV, FcRH5 is a candidate to be this unidentified gene. One can speculate that perturbation of FcRH5 expression and thus function during EBV-driven B-cell proliferation might disregulate B cells, thus contributing to B-cell malignancies.…”
Section: Ebna2 Induces Fcrh5 Expression Through Cbf1 4437mentioning
confidence: 99%
See 1 more Smart Citation